2020
DOI: 10.1111/een.12967
|View full text |Cite
|
Sign up to set email alerts
|

What drives gallers and parasitoids interacting on a host plant? A network approach revealing morphological coupling as the main factor

Abstract: 1. Ecological interaction networks, those built from linking interacting species in a biological community, can be structured according to neutral factors, like abundance, or depend on species distribution in space, time, or functional aspects of interacting species. 2. Gall inducers are a specialized guild of herbivores producing a structure serving as shelter, food, and defence against natural enemies. Interactions between galling insects and their parasitoids can become complex; studies analysing processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…As previously reported, we found that the parasitoid communities were mostly composed of few very abundant generalist parasitoid species, whereas the specialist parasitoid species occurred in higher number, but in low abundance (De Araújo & Maia, 2021;Luz et al, 2021;Paniagua et al, 2009). Most of the generalist parasitoid species occurred in burned scenarios, as we expected, but we failed to detect any changes directly related to fire effects.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…As previously reported, we found that the parasitoid communities were mostly composed of few very abundant generalist parasitoid species, whereas the specialist parasitoid species occurred in higher number, but in low abundance (De Araújo & Maia, 2021;Luz et al, 2021;Paniagua et al, 2009). Most of the generalist parasitoid species occurred in burned scenarios, as we expected, but we failed to detect any changes directly related to fire effects.…”
Section: Discussionsupporting
confidence: 82%
“…Some studies have found that parasitoid richness varies among galling insect communities that differ in species richness and composition (Dawah et al, 1995; Nyman et al, 2015; Paniagua et al, 2009). Moreover, according to the studies addressed in the Neotropical region, most of the galling insects appear to be attacked by specialist parasitoid species (De Araújo & Maia, 2021; Luz et al, 2021; Paniagua et al, 2009). Therefore, changes in galling insect species composition may be strongly reflected in the specific composition of the associated parasitoids (László & Tóthmérész, 2013; Nyman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For each parasitoid morphospecies, we measured 1-3 individuals per region per host morphotype. We measured body size from the tip of the thorax to the end of the abdomen, the area of the wing, length of external ovipositor, width of thorax, and size of tibia (all in mm) (45). Since body size correlates with all other traits, we divided trait measurements by body size.…”
Section: Host-parasitoid Interaction Traits and Phenologymentioning
confidence: 99%
“…At the same time selection favors traits in parasitoids that help them evade host defenses (42)(43)(44)(45). Traits include morphological features such as body size that can facilitate host defense or ovipositor size that can facilitate parasitoid attack (44)(45)(46). Phenology is also essential to interactions between insect hosts and parasitoids, as successful development for parasitoids requires that they attack hosts during discrete time windows, outside of which their development will not correspond with host resources (43,47).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation